DINAMIKA PSIKOLOGIS INTERAKSI KONSEP DIRI DAN IDENTITAS ONLINE - , LIDIA SANDRA, Prof. Drs. Koentjoro, M.BSc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Interaction of self concept and online identity is the analysis unit of this research. This study aims to explore the psychological dynamics of the interaction of selfconcept and identity online of internet users in Indonesia. Applying a concurrent mixed method, this research answers three main questions "how is the interaction of self-concept and online identity of Internet users in Indonesia?", "what are the psychological factors in the interaction" and "how is the psychological dynamics of this interaction?". Quantitative data collection using questionnaires and scales, while qualitative using observation, interviews and focus group discussions. Analysis for the quantitative data involved cross tabulation, exploratory factor, anova, discriminant, multidimensional scaling and SEM analysis while qualitative using grounded theory analysis. This study was conducted toward internet users in Indonesia from late childhood, teenagers and young adults age category. Result of this study suggested that the interaction of self-concept and online identity is a cycle of identity construction consisting of five elements, namely goal, activity, object, outcome and impact. Psychological factors found in this interaction are self-exploration, impression management, self-exposure, interaction manifest, interaction consideration, perceived social influence, perceived value of the internet and perceived internet impact. Empirical data demonstrated that the dynamics of the interaction follows a certain law: a. self-concept holds a central role in this interaction. Psychological factors could not be isolated from social factors. This is indicated by the strong impact of perceived social influence toward psychological well-being of Internet users. Positive perceived value of the Internet surprisingly demonstrated a positive impact toward the psychological well-being of Internet users